Evaluasi Tingkat Kapabilitas Tata Kelola Teknologi Informasi dengan Framework COBIT 5 pada proses DSS02 dan DSS03 di PT Hexindo Adiperkasa Cabang Balikpapan - Erlan Erlangga; Andi Reza Perdanakusuma; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
PT. Hexindo Adiperkasa Balikpapan Branch is a company engaged in heavy equipment trading industry and provides services to customers. PT. Hexindo Adiperkasa Balikpapan Branch has utilized IT in data communication network to assist daily operational in company. The existence of information technology used in company, besides provide benefits it also cause risk which known as IT incidents to company. Managers must manage every IT incident with effective and efficient in order to prevent any bad impact that could hampered business operations. Based on these problems, researcher evaluate the management of information technology service management at PT. Hexindo Adiperkasa Balikpapan Branch to assess the company's maturity in managing information technology. In accordance with problems as mentioned above, author used the COBIT 5 framework and DSS (Deliver, Service, and Support) domain that focuses on DSS02 (Managing Service Requests and Incidents) and DSS03 (Problem Management) processes. Based on the assessment results, DSS02 is at capability level 0 and DSS03 is at capability level 0. The target capability for DSS02 and DSS03 is at level 1. It is recommended that the target capability which had been achieved are mapped in the roadmap with a span time of 3 years.